THE EFFECT OF BUSINESS CAPITAL, ACCOUNTING KNOWLEDGE, AND THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEMS ON THE PERFORMANCE OF MSMEs IN DENPASAR CITY - Ni Luh Made Widya Arini Putri; Henny Triyana Hasibuan (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The performance of MSMEs is considered one of the benchmarks for the success of a business entity in achieving its objectives. Improved performance will bring progress for a business to survive in increasingly intense competition. This study aims to obtain empirical evidence regarding the effect of business capital, accounting knowledge, and the implementation of accounting information systems on the performance of MSMEs in Denpasar City. The population in this study consists of MSMEs spread across Denpasar City, totaling 69,491 units. The sampling method used was probability sampling with the disproportionate stratified random sampling technique. The number of samples based on the Slovin formula was 100. Data were collected by distributing questionnaires to 100 MSMEs operating in Denpasar City. The analytical technique employed was multiple linear regression analysis using SPSS 26 for Windows. Based on the results of the analysis, business capital has a positive and significant effect on MSME performance, and accounting knowledge also has a positive and significant effect on MSME performance. However, the implementation of accounting information systems has no effect on MSME performance.